Actors of Community Development: Insider and Outsider Perspectives. Issue 1 (2nd January 2022) - Dahal, Bibek; White, Pamela
Abstract: The diverse socio-economic and geographical situation of Nepal contributes to the complexity of community development. In such varied contexts, holistic community development faces many challenges, addressing cross-cutting issues like health and education, which may be viewed differently by men and women, as well as different castes, ethnicities, economic status, political associations and religions. The community's well-being must be the central focus of every development intervention, yet there is no one opinion that reflects the diversity of opinions within every community. How can community development practitioners listen to all viewpoints and find an accepted method to achieve grassroots development in such a complex environment, when they themselves come from diverse backgrounds and education, and bring their own attitudes and opinions? The central focus of this study was to investigate the reflective practices of community development at the grassroots level of rural Nepal. The study investigates the practices and perceptions of community development practitioners and their reflexivity regarding their life experiences and efforts to adequately relate to diverse communities. For this, critical reflective inquiry has been used. Practitioners with extensive experiences were chosen as research participants for that purpose. The life experience of both authors and the practitioners is interpreted through the lens of actor perspective on community development. Additionally, we consider how the insider and outsider perspectives of development practitioners may influence their work. Three key elements with the potential to directly interference the process of community development in rural Nepal were explored: local people as subjective forms of beneficiary; community development practitioners as mediators of interventions; and development policies as a roadmap of community inclusion. The dynamic involvement of these three elements is crucial to reach goals envisioned by community development interventions, yet often the practitioners are ignored. The paper concludes that the success of such interventions rests upon the active and reflective intercourse of this triangulation.